PERAN UNDP DALAM PENCAPAIAN MILLENNIUM DEVELOPMENT GOALS UNTUK MENANGGULANGI KEMISKINAN DAN KELAPARAN DI INDIA - Dewinta Stanie; Den Yelta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study discusses the role of UNDP in the achievement of the Millennium Development Goals (MDGS)to reduce poverty and hunger in India. UNDP is the UN specialized agency that has the responsibility to monitor the achievement of the MDGs in developing countries. In addition, UNDP also has a duty to address the problem of poverty in developing countries. Despite being the second greatest country in the world with impressive economic growth, but the rate of poverty and hunger in India is still high.As a member of UN states, India signed the Millennium Declaration adopted by the UN in 2000 in the agreement that resulted to the Millennium Development Goals. The MDGs are a framework relating to the global challenges that will be faced by countries in the future. MDGs aim to overcome global challenges through the cooperation of developed countries and developing countries.The research focuses is on achieving the MDGs in India in overcoming poverty and hunger is on the first goal. In achieving the first goal, UNDP’s role to assist the government of India in reducing poverty through programs and policies made by the Indian government. The assistances are in the form of provision of funds, institutional development, and policy development skills. However, to achieve the first objective of the MDGs, India is faces several challenges and obstacles.Keywords: India, Millennium Development Goals, UNDP, Poverty, Hunger, Undernutrition